The impact of commercialization of rice on household welfare in rural Viet Nam - Chiara Cazzuffi; Andrew D. McKay; Emilie Perge (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The past 30 years have seen a consistent increase in agricultural commercialization in rural Viet Nam, at the same time when rural residents have moved increasingly into non-agricultural activities. The contribution of the latter to welfare improvement and poverty reduction is well known; in this paper we investigate the extent to which increased agricultural commercialization has also contributed to improving welfare levels. For this purpose, we use the five-wave Viet Nam Access to Resources Household Survey (VARHS) panel data set from 2008-16 to consider the specific impacts of increased commercialization of rice, Viet Nam's dominant crop. We use three measures of welfare and two measures of agricultural commercialization, and find a significant impact of commercialization on household assets, a longer term welfare measure. However, we do not find much impact on household income and food consumption. The results also show heterogeneous effects across different types of households, with particularly large impacts for those who are frequent sellers.
Keywords: O12; O13; Q12; Q13; 330; Commercialization; smallholders; rice; Viet Nam